Communication on the World Wide Web: Designing an Effective Homepage - Tom Kelleher; Michelle Henley; Debra Gennarelli; Linda Hon (Journal of Applied Communications, 1997)
The purpose of this study was to examine the content and structural features of a World Wide Web homepage with the explicit goal of making recommendations for how a homepage should be designed.